Bubble velocity in horizontal and low-inclination upward slug flow in concentric and fully eccentric annuli. (31st December 2018) - Ibarra, Roberto; Nossen, Jan
Highlights: Taylor bubble velocity was obtained for concentric and fully eccentric annuli. The effect of annulus eccentricity on the bubble velocity was investigated. Individual bubble velocities and slug shapes were analysed. Full pipe models under-predict data for high Froude numbers. A new approach is presented for annuli showing excellent agreement with data. Abstract: The Taylor bubble velocity for gas–liquid flows, which is of great importance in multiphase flow models, has been thoroughly studied for a wide range of conditions in full pipe flows. The applicability of models developed for these full pipe systems to flows in annuli has not been fully verified as very little data are available. This work presents experimental data on concentric and fully eccentric horizontal and 4° upward annulus for gas–liquid flows at high-pressure (400 kPa, absolute). The test fluids are water and Exxsol D60 as the liquid phases and sulphur hexafluoride (SF6 ) as the gas phase. The test section consists of a 45 m long PVC pipe with an annulus pipe diameter ratio of K  = 0.505 and an inside diameter of the outer pipe of 99 mm. Gamma densitometer sensors have been used to measure the instantaneous cross-sectional average holdup at different locations along the test section. Results show that the bubble velocity follows a linear trend, similar to that observed in full pipe systems, with a critical Froude number at Fr M, C ≈ 3.3. For Froude numbers lower than the critical value, the bubble velocity is well predicted by models developed for full pipe using the hydraulic diameter. For higher Froude numbers, a new correlation has been developed based on the experimental observations with excellent agreement for all cases studied.